Alternative screening method for drought tolerance in barley genotypes - Were, Javan Omondi; Ochuodho, Julius Onyango; Rop, Nicholas Kipkemboi; Gyawali, Sanjaya (Journal of Scientific Agriculture, 2021)
Lack of genetically stable and durable drought tolerant winter and spring barley genotypes is one of the main contributing to low and unpredictable yields in Kenya and other parts of the world despite annual release of new and high yielding varieties. Therefore, the study was set to identify genotypes exhibiting tolerance to drought through physiological and phenotypic approaches. A total of 32 genotypes were planted in split-plot arrangement in completely randomized design replicated thrice. Genotypes were maintained under 20% and 80% field capacities. Phenotypic and physiological data were collected, converted to ratios then analyzed on Genstat version 14.1 VSN International Ltd at a 5% level of significance. Significant differences were observed in winter and spring barley in terms of growth, tillering ability, grains formed per spike, 1000 seed weight and MSI (p < 0.05). Spring barley expressed higher tolerance to drought than winter barley especially in terms of height, number of grains per spike and seed weight. Water deficiency in cells and tissues might have altered and inhibited physiological and biochemical processes. The phenotypic and physiological methods corresponded and confirmed tolerance to drought in most winter and spring genotypes grown in Kenya.